Out-of-Plane Coordinated Porphyrin Nanotubes with Enhanced Singlet Oxygen Generation Efficiency - Zhao, Qiang (Sci Rep, 2016)
A supramolecular porphyrin nanotube displaying J-aggregation feature was constructed by out-of-plane coordinated bismuth-porphyrin. Significantly, compared to traditional J-aggregated porphyrin suffering from fluorescence and singlet oxygen quenching, the nanotube exhibits excellent bio-imaging ability and enhanced production efficiency of singlet oxygen. The out-of-plane structure of bismuth to porphyrin makes the aggregation an appropriate material for theranostics. Furthermore, it is also a potential radio-therapeutic drug owing to the presence of radio-active bismuth. Thus, the self-assembly of out-of-plane coordinated porphyrin can be a facile approach toward effective therapy of tumors and other diseases.